CASE REPORT: VAN WYK-GRUMBACH SYNDROME: HYPOTHYROIDISM PRESENTING AS PRECOCIOUS PUBERTY - Ahmad, Hazirah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Acquired causes of hypothyroidism such as Hashimoto’s thyroiditis is mostly insidious and often goes undetected, unless there is concomitant thyroid gland enlargement or profound hypothyroid symptoms. Precocious puberty in girls is a rare cause of acquired hypothyroidism. CASE We report an 8 year-3-month-old female of Chinese-Indian descent, who presented with precocious puberty (bilateral breast budding, axillary hair, and pubic hair) about 6 months prior, with the mother’s concern of poor learning in school. There were no other symptoms of puberty such as vaginal discharge or growth acceleration. She was adopted at 6 months old, thus, there is uncertainty about her biological family history. Her height was at the 25th centile and weight at 75th centile. She had a single café-au-lait spot at the right thigh, with Tanner stage 2 breasts, axillary hair, and pubic hair. She also had mild scoliosis with no other skeletal deformities. She had no thyroid gland enlargement but her facial expression was dull. Her blood investigations revealed pre-pubertal levels of gonadotrophins with undetectable estradiol, normal prolactin and negative b-HCG screen. Her thyroid function revealed markedly increased TSH (>100mIU/L) with severely low fT4 (<5.4 pmol/L). Her thyroid peroxidase antibody (anti-TPO) level was 131 IU/ml (<35). Ultrasound of the thyroid showed features in keeping with autoimmune thyroiditis with incidental thyroglossal duct cyst. Upon further questioning, the mother did recall prominent neck swelling since the past 2 years. Following L-thyroxine initiation, her thyroid function normalized and she showed significant improvement in height (she grew 10 cm/year) with progression of puberty. Her last bone age was 10 years old (CA: 9 year and 6 months). CONCLUSION Van Wyk-Grumbach syndrome is a relatively uncommon cause of pseudo-precocious puberty that often skips detection. Thyroid assessment is recommended in a girl presenting with precocious puberty, even in the absence of goiter. Timely diagnosis and treatment with L-thyroxine normalizes thyroid function and significantly improves linear growth.